Load and temperature influence on the post-fire mechanical properties of steel reinforcements. (October 2021) - Lapuebla-Ferri, A.; Pons, D.; Romero, M.L.
Abstract: An experimental study was carried out to evaluate the residual mechanical properties of steel reinforcements after their exposure to elevated temperatures. In order to reproduce real loading conditions, specimens were simultaneously subjected to a load level and a thermal cycle consisting of heating up to a target temperature and cooling back to room temperature. The target temperature was a percentage of the critical temperature, i.e., the temperature at which a specimen breaks when it is subjected to a constant tensile load and an increasing temperature at a constant rate. After that, the residual mechanical properties were obtained submitting the specimens to tensile testing until failure. Critical temperatures for each load level were obtained by means of transient-state tests. In parallel, unloaded specimens were subjected to the same thermal cycle for comparison purposes, and for the same reason steady-state tests were also performed. Results indicated that the residual mechanical behaviour of reinforcing bars depended not only on the maximum temperature reached, but also on the load level that was bearing during the thermal cycle. Depending on this combination of variables, the code requirements for a given ductility class of a reinforcement may not be satisfied in a post-fire situation. Considering the lack of information in this issue, the obtained data can be helpful in the assessment of reinforced concrete structures after a fire. Graphical abstract: The residual mechanical properties of steel reinforcements after its exposition to elevated temperatures were obtained experimentally. Four test types were performed: 1) steady-state tests to obtain the properties of reinforcements at high temperatures; 2) transient-state tests to measure the critical temperature at which a reinforcement fails when it is subjected to the simultaneous action of load and increasing temperature; 3) tests on unloaded specimens under a thermal cycle (heating and cooling back to room temperature) and 4) the same thermal cycle acting simultaneously with an applied load. Results indicated that residual mechanical properties of reinforcing bars, especially the ductility, depended not only on the maximum temperature reached, but also on the load level that was bearing during the thermal cycle. The obtained data can be helpful in the assessment of reinforced concrete structures and steel-concrete composite structures after a fire. Unlabelled Image Highlights: Residual material properties of loaded and unloaded steel reinforcements after a fire are obtained by experimental testing. Post-fire ductility of loaded steel reinforcements is studied. The pool of available experimental results for steel reinforcement bars at elevated temperatures are increased.